The Metaphysic of Encounter of Space at the Meet of Persian Miniature with Renaissance Painting - abdollah aghaie; marziye piravi vanak (Metaphysics, 2015)
Persian miniature, in its turbulent history, has been influenced by a variety of visual traditions. From the middle of the Safavid period, by increasing communications with Western countries, visual traditions of Renaissance came to Iran in different ways. Fundamental changes in Persian miniature's position and form in this period, shows that its contact with renaissance painting, has been a structural facing. The most fundamental part of this facing is seen between two disharmonious understandings of space's concept. The main question of this article is "The Why" of this facing in pictorial space. The approach of this article is to answer to this philosophical question; therefore it is tried to explain this facing in a conceptual way by surveying metaphysics foundations. For this purpose, on the one hand, using the concept of "mathematical matter" in Heidegger's philosophy, it is shown that how the elevation of modern metaphysics caused the emergence of a "quantitative" space in renaissance painting and on the other hand, by analyzing the pictorial, Persian miniature space, it is shown  that how the" qualitative" space of Iranian painting is shaped via gathering its content elements against the absolute and abstract space of renaissance painting